PERANAN KEPUASAN KERJA SEBAGAI PEMEDIASI PENGARUH KEPEMIMPINAN PARTISIPATIF TERHADAP KINERJA KARYAWAN PADA PT. SEJAHTERA INDOBALI TRADA DENPASAR - I Gede Made Khrisna Paramitha Putra; Anak Agung Dwi Widyani; Ni Putu Ayu Sintya Saraswati (VALUES, 2021)
This study aims to determine the effect of participatory leadership on performance, participatory leadership on job satisfaction, job satisfaction on performance, and the role of job satisfaction as a mediator of the influence of participatory leadership on employee performance at PT. Prosperous Indobali Trada. This study took 30 respondents at PT. Prosperous Indobali Trada. The data were analyzed using the Partial Least Square (PLS) analysis technique to answer the problem formulation with the help of the Smart PLS 3 program. The results of testing the hypothesis showed that the variables: 1). Participatory Leadership has a positive and significant effect on employee performance, 2) Participatory Leadership has a positive and significant effect on job satisfaction, 3). Job satisfaction has a positive and significant effect on employee performance, and 4). Job satisfaction is a mediating variable of positive influence between Participatory Leadership on employee performance.